Nitrogen Fertilisation Increases Specific Root Respiration in Ectomycorrhizal but Not in Arbuscular Mycorrhizal Plants: A Meta-Analysis - Bicharanloo, Bahareh; Cavagnaro, Timothy R.; Keitel, Claudia; Dijkstra, Feike A. (Frontiers in Plant Science, 2021)
Plants spend a high proportion of their photosynthetically fixed carbon (C) belowground to support mycorrhizal associations in return for nutrients, but this C expenditure may decrease with increased soil nutrient availability. In this study, we assessed how the effects of nitrogen (N) fertiliser on specific root respiration (SRR) varied among mycorrhizal type (Myco type). We conducted a multi-level meta-analysis across 1,600 observations from 32 publications. SRR increased in ectomycorrhizal (ECM) plants with more than 100 kg N ha−1 applied, did not change in arbuscular mycorrhizal (AM) and non-mycorrhizal (NM) plants, but increased in plants with a dual mycorrhizal association in response to N fertilisation. Our results suggest that high N availability (>100 kg N ha−1) could disadvantage the growth of ECM plants because of increased C costs associated with maintaining higher root N concentrations, while the insensitivity in SRR by AM plants to N fertilisation may be because AM fungi are more important for phosphorus (P) uptake.